1997
DOI: 10.1021/om970715j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and NMR Studies of Indenyl Hapticity and Rotational Barriers in the Complexes (η-1-R-Indenyl)Ni(PPh3)(X) (R = H, Me; X = Cl, Me)

Abstract: The relative trans influences of Cl and Me in the complexes (1-Me-indenyl)Ni(PPh 3 )Cl and (1-Me-indenyl)Ni(PPh 3 )Me lead to different solid state hapticities for the 1-Me-indenyl ligands. Comparing the solution NMR data for these complexes and the energy barriers to the rotation of the indenyl ligands in their unsubstituted analogues demonstrates that solid state hapticities are preserved in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…The 1 H NMR spectrum of compound 2 exhibits a single resonance at δ 5.97 for the protons attached to the C 5 ring of the 2-methylindenyl ligand, indicative of C s symmetry. 13 C-{ 1 H} NMR data are useful for assessing indenyl hapticity in complexes, 12 in particular the parameter ∆ δ. This parameter represents the difference in chemical shift between the 13 C-{ 1 H} NMR resonances of the ring-junction carbon atoms in an indenyl complex and in "free" indenyl (i.e.…”
Section: Preparation and Spectral Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectrum of compound 2 exhibits a single resonance at δ 5.97 for the protons attached to the C 5 ring of the 2-methylindenyl ligand, indicative of C s symmetry. 13 C-{ 1 H} NMR data are useful for assessing indenyl hapticity in complexes, 12 in particular the parameter ∆ δ. This parameter represents the difference in chemical shift between the 13 C-{ 1 H} NMR resonances of the ring-junction carbon atoms in an indenyl complex and in "free" indenyl (i.e.…”
Section: Preparation and Spectral Characterisationmentioning
confidence: 99%
“…Very recently, several neutral and cationic nickel indenyl derivatives have been reported. [10][11][12][13][14][15] Given the existing relationship between allyl and indenyl complexes due to the so called "indenyl effect" (relatively facile ring slippage of the indenyl ligand involving change from η 5 to η 3 coordination), such species have also proven effective as catalysts for the oligomerisation of ethylene, 11 or even the polymerisation of phenylacetylene. 15 Nickel indenyl complexes can be considered as a link between η 5cyclopentadienyl and η 3 -allyl derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of (1-Me-Ind)(PPh 3 )Ni−CC−Ph, 1 , can be accomplished via a metathetic reaction between the known Ni−Cl precursor and Ph−CC - Li + in benzene; addition of hexane precipitates the desired product as a yellow-brown solid in ca. 70% yield (eq 1).…”
Section: Resultsmentioning
confidence: 99%
“…Monitoring the reaction of 1 and 2 with MAO in C 6 D 6 revealed that these complexes are converted to species displaying the characteristic 31 P{ 1 H} and 1 H NMR signals of the corresponding Ni−Me analogues; addition of Ph−CC−H to this mixture led to the formation of PPA. On the other hand, similar experiments revealed that the isolated samples of the Ni−Me species cannot catalyze the formation of PPA in the absence of MAO.…”
Section: Resultsmentioning
confidence: 99%
“…5 nm indicate nearly η 3 hapticity). 19 As seen from Table 1, the structures of (1-R-Ind)Ni(PPh 3 )Cl exhibit a progressively more distorted coordination of the indenyl ring from ethyl to cyclopentyl and then to benzyl. Meanwhile, both of Ni-Cl and Ni-P interactions show a weak trend in the same turn.…”
Section: Effect Of Ligands On the Structures Of Indenylnickel(ii) Commentioning
confidence: 93%